PERLINDUNGAN HUKUM TERHADAP DEBITUR WANPRESTASI YANG DIAKIBATKAN OLEH PANDEMI - Adhyaksa, Putu Pratama Wira Wira; Priyanto, I Made Dedy (Kertha Negara : Journal Ilmu Hukum; Vol 11 No 3 (2023), 2023)
The purpose of this study is to examine the problems that are happening in Indonesia, especially when the pandemi has hit like now. This study uses normative legal research methods with statutory and comparative approaches. The results of the study show that the government is taking a path to make new regulations as an effort to overcome the crisis that occurred in Indonesia, namely the issuance of OJK Regulation Number 11 /POJK.03/2020 concerning "National Economic Stimulus as a Counter Cyclical Policy on the Impact of the Spread of Corona Virus Disease 2019". It is hoped that this regulation can at least be a breath of fresh air for people who are in trouble because they are dealing with banking businesses